SISTEM PENDUKUNG KEPUTUSAN UNTUK MENENTUKAN LOKASI BUDIDAYA RUMPUT LAUT MENGGUNAKAN METODE MATCHING BERDASARKAN KONDISI PERAIRAN DI MADURA - , HARI TOHA HIDAYAT ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Determining a location was the very important first step in gaining success in seaweed cultivation bussiness. The growth of the seaweeds was highly dependent of local ecological condition. The study aimed at developing a decision supporting system with a weighting and matching model in determining seaweed cultivation location based on local waters condition. The process in determining the location of the seaweed cultivation was carried out by firstly entering waters criteria of wave height, temperature, salinity, water clarity, flow velocity, CO2 and DO into a weighting model to give appropriateness value and secondly entering turbidity value, total suspended materials (TSM) and chlorophylls that were subsequently used in a matching model.